Pengaruh Kondisi Lingkungan Optimum Selama Pertumbuhan Jamur Merang (Volvariella Volvacea) Terhadap Proses Delignifikasi Limbah Tandan Kosong Sawit (Tks) - Andhini Getha Kusuma; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The empty fruit bunch (EFB) is a solid waste from palm oil processing with the highest percentage of 23% per ton of the fresh fruit bunch (TBS), which has not been optimally utilized from the palm oil industry. EFB have 15-30% lignin components and complex chemical composition which is difficult to be degraded. To be easily converted into a simpler element, the bunches have to be firstly degraded. The utilization of the empty bunches as a medium to the growth of paddy straw mushroom (Volvariella volvaccea) is expected to degrade the content of lignin. The mushroom (Volvariella volvacea) produces extracellular enzymes in the form of LiP and MnP in degrading lignin. This study aims to study the effect of environmental conditions on the growth of straw mushrooms (Volvariella volvacea) on lignin degradation. This study has variation of seed mushroom weight of which 250 gr, 350 gr and control. The best results show that the highest percentage of lignin declining was found in the increasing weight of 250 gr paddy straw mushroom seeds which was 61%, with the achievement of optimum environmental conditions such as temperatures in the range 27.2-30.6 0C, pH 7.0-7.36 and water content of 42-85.2%. The conclusion of this study is that the optimum environmental conditions during the growth of the mushroom (Volvariella volvacea) become an important factor in the process of lignin degradation in the waste of EFB. Keywords : EFB, Lignin, pH, Temperature, Moisture content, Degradation